A Study On Stabilization of Soils by Using Egg Shell Powder (International Journal of Innovative Research in Engineering & Management, 2023)
Using alternative materials, which have  better engineering quality than traditional materials and are  more cost-effective, has received a lot of attention recently.  One of the most crucial components in many building  projects, such as earth canals and earth dams, is soil. The  fact that soil might offer all the resistant qualities required  for a project highlights the value of several techniques used  to enhance soil quality. The vast majority of construction  projects employ clay soil. Because clay soils, especially soft  clay soils, have good plastic qualities, their shear strength,  compressive strength, and volume changes decrease as  moisture content rises. Structures generally suffer  permanent harm as a result of these issues, which  emphasises how crucial soil improvement is. The use of  such refuse and industrial wastes and their subsidiary  products as alternatives to construction materials may  effectively contribute to environmental preservation and  minimize their negative effects on the Environment,  especially in light of the millions of tonnes of waste  produced annually across the nation, which not only poses  the problem of disposal but also adds to environmental  contamination and health risks. In the current study,  eggshell powder was utilized as a waste to mix with soil in  order to examine clay soil's index characteristics,  compaction, and shear strength at various mixed  proportions. The shear strength of soils that had already  been tested was then contrasted with experimental  specimens that had been combined with various ratios of  eggshell powder.
Keywords: Stabilization; Soil; Eggshell Powder